Minimizing the memory usage with parallel out-of-core multi-frontal direct solver - Paszyński, Maciej (Computer Assisted Methods in Engineering and Science, 2017)
This paper presents the out-of-core solver for three-dimensional multiphysics problems. In particular, our study focuses on the three-dimensional simulations of the linear elasticity coupled with acoustics. The out-of-core solver is designed with three principles in mind. First, to store the dense matrices associated with the nodes of the elimination tree with blocks related to nodes of the mesh, where many degrees of freedom may be located in the case of multiphysics computations with high order polynomials. The second principle is to minimize the memory usage. This is obtained by dumping out all local systems from the entire elimination tree to the disk during the elimination stage. The local systems are reutilized later during the backward substitution stage. The third principle is that the communication in the parallel version of the out-of-core solver occurs through the parallel file system. The memory usage of the solver is compared against the state-of-the-art MUMPS solver.